Efektivitas Aplikasi Quizizz Terhadap Keterampilan Membaca Bahasa Jerman Siswa Kelas XI SMA Swasta Taman Siswa Pematangsiantar - Sihotang, Cindy Pratiwi; Simanjuntak, Tarida Alvina; Purba, Lydia (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the effectiveness of the Quizizz application on German reading skills in class XI students at Taman Siswa Private High School, Pematangsiantar. This research uses quantitative methods with a pre-experimental design and a One Group Pretest-Posttest research design for one experimental class. The research population was class XI IPA 1 Taman Siswa Pematangsiantar Private High School, consisting of 120 people. Based on simple purposive sampling technique. The sample in this research was 28 students from class XI IPA 1. The data collection technique is in the form of a test essay by carrying out the Pretest stage, treatment by applying the Quizizz application media and Posttest, so research data is produced. The research results showed that there was a significant increase in students' reading skills after implementing the Quizizz application, with an average Posttest score of 86.61 compared to an average Pretest score of 40.71. Statistical tests show that the Quizizz application is effective in improving reading skills, as evidenced by the results of the hypothesis test and the N-gain value of 78% which is included in the effective category. Then the Paired Sample T-Test hypothesis test shows significant results with a value of 35.652 < 0.381, so it can be concluded that H0 is rejected and H1 is accepted. In conclusion, the Quizizz application learning media is effective on the reading skills of class XI students at Taman Siswa Pematangsiantar Private High School.